Cochlear implants in Japan: Results of cochlear implant reporting system over more than 30 years. Issue 4 (August 2021) - Kashio, Akinori; Takahashi, Haruo; Nishizaki, Kazunori; Hara, Akira; Yamasoba, Tatsuya; Moriyama, Hiroshi
Abstract: Objective: To conduct a longitudinal national survey of cochlear implantation (CI) in Japan from 1985 through 2017. Methods: A retrospective analysis of adult and pediatric CI cases from 1985 to 2017 using the Oto-Rhino-Laryngological Society of Japan CI registration database was conducted. Surgical statistics were obtained, including number of surgeries, age, implanted side, facilities, and preoperative threshold levels for CI. Results: Since 1985, more than 11, 100 CI surgeries have been conducted in Japan. The number exceeded 500 in 2005 and 1, 000 in 2015. Since 2007, pediatric cases consistently surpassed adult cases until 2016. More facilities meet criteria for conducting CI as determined by Ministry of Health, Labor and Welfare and have now reached more than 100. Adult patients over 70 years old have become proportionally higher. Age at implantation steadily reduced in accordance with modifications of Japanese CI guidelines for children but is still not comparable to that in other developed countries. Although the number of CI surgeries for patients with moderate to severe hearing loss increased in the past ten years, the proportion was small. Conclusions: The CI database in Japan is quite unique in that it documents almost all the CI surgeries in Japan, allowing us to summarize the present situation as follows: fewer CI surgeries occur than are necessary, and children receiving implants are older than those in other developed countries. Continuous improvement of CI awareness is needed in Japan.